Human-leukocyte antigen typing in Javanese patients with recurrent aphthous stomatitis - Diah Savitri Ernawati; Bagus Soebadi; Desiana Radithia (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Recurrent aphthous stomatitis (RAS) is a common oral disorder that despite extensive researches, the etiology of this phenomenon is still unknown. Because this phenomenon has been observed more often in families than in individual cases, genetic influence has been investigated in most researches. Purpose: The aim of study was to evaluate the association between human leukocyte antigen (HLA) and RAS in Javanese more precisely. Method: The analysis of HLA-A, and HLA-B in 85 Javanese RAS patients and 71 healthy control subjects, were performed by using the standard NIH microlymhocytotoxicity technique. Immunohistochemistry was performed for identification of HLA-DR and HLA- DQ antigen using monoclonal antibodies anti HLA-DR and DQ. Result: Our result revealed a close association between HLA-A9 and HLA-B35 RAS subject. A significant increase in the frequency of some antigens such as HLA-A9 (72,94%, p < 0,05;RR = 2,21), HLA-A24 (65,82%; RR = 1,24) and HLA-B35 in subjects with RAS was observed. Analysis with Immunohistochemistry HLA-DR, HLA-DQ is expressed on the surface of epithelial cells membrane of oral mucosa and macrophages in both major and minor RAS patients. Conclusion: HLA antigens are involved in susceptibility to RAS and the phenotypes were difference with other previous studies. HLA- linked genetic factors may play a role in the development of RAS.Latar belakang: Stomatitis aftosa rekuren (SAR) merupakan salah satu gangguan di rongga mulut yang paling sering terjadi. Fenomenapenyakit ini masih belum jelas dan masih membutuhkanpenelitian yang lebih lanjut. Faktor keturunan lebih sering daripada kasus individual. Pengaruh faktor genetik telah diteliti oleh beberapapeneliti. Tujuan: Tujuan penelitian ini untuk mengetahui adanya kaitan HLA dengan SARpada suku jawa secara lebih tepat. Metode: Analisis HLA-A, HLA-Bpada 85penderita RAS dan 71 penderita kontrol yang berasal dari suku Jawa dihitung dengan menggunakan teknik NIH Micro Lymphocytotoxicity. Teknik Imunohistokimia dilakukan untuk mengidentifikasi antigen HLA-DR, HLA DQ dengan menggunakan antibodi monoklonal HLA-DR & DQ. Hasil: Menununjukkan hubungan yang kuat antara HLA-A9 dan HLA-B-35 pada pasien SAR. Terdapat peningkatan yang signifikan dari beberapa antigen seperti HLA-A9 (72,94%, p < 0,05, RR = 2,21), HLA-A24 (65,82%, RR = 1,24) dan HLA-B35 pada pasien SAR yang di observasi. Analisis dengan Imunohistokimia tampak HLA-DR, DQ diekspresikan pada permukaan membran sel dan makrofag pada pasien SAR mayor maupun minor. Kesimpulan: Antigen HLA terlibat dengan kepekaan terjadinya RAS, dan fenotipnya berbeda dengan hasil penelitian sebelumnya HLA dan faktor genetik berperan penting pada terjadinya SAR.